The Role of Micro, Small, and Medium Enterprises (MSMEs) in Supporting Indonesia’s Economic Resilience - Wahyudi, Ahmad Shohibboniawan; Yulivan, Ivan; Rahman, Aditya (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
The current entrepreneurship rate in Indonesia is only 3.47%, much lower than neighboring countries such as Singapore, Thailand, and Malaysia. This shows that there is a significant gap in the development of entrepreneurship in Indonesia, which is very important to drive economic growth. Entrepreneurship plays an important role in job creation, innovation, and diversification of economic income sources. In this context, Micro, Small, and Medium Enterprises (MSMEs) are the main pillars of sustainable economic growth and contribute positively to improving the community’s quality of life. This study aims to review the role of MSMEs in contributing to national economic resilience, both when the economic situation is stable and dynamic. This study uses a descriptive approach based on the data and information obtained. This study found that MSMEs have a crucial role in improving people’s welfare and supporting economic growth in Indonesia, which affects national economic resilience. MSMEs also contribute significantly to the development of creativity and innovation and are able to adapt to dynamic market changes. The government should provide facilities and access to digital technology, export markets, and financing. Supportive policies and simpler regulations must be improved to strengthen the MSME sector. A holistic approach is needed to implement cross-sector collaboration involving government, business, academics, and communities to support sustainable economic growth.